BEBERAPA CATATAN TENTANG EBONI DI SULAWESI - Wesman Endom (Jurnal Penelitian Hasil Hutan, 1994)
Central Sulawesi  is one of the areas where  Eboni species  (Ebony spp) grows naturally.  The other areas are North Sulawesi  and North Maluku. The species have valuable  wood  and many people like them due to their artistic and black appearance.In the  last few  years,  the species  heve been decreasing  and  today  they can  be categorized  as  endangered  or  at  least as  in. vulnerable codition. Since 1988, in accordance to the Ministry of Forestry Decision No 988/Menhut-IV/1988, the harvesting of Eboni had been banned.The observation of the logged forest  area shows that  the number of Ebony trees in the field  is very small.  To  protect  the species from  their extinction,  the strict regulations are  required and the activities of the planting and tending need to be intensifed.The other observation result are as follows :1. Most felling  activity  had been  carried out on the  small  diameter  of  35 cm while the  trees  are still growing  well to reach  larger diameter  (60 cm or more).2. Part of the  wood  utilized  was only heartwood  that had  the  volume  of about 42%  ot total  volume.  Therefore,  to  have  larger volume, is  better  to harvest  only  big trees  of diameter  60 cm or more.3. THe clear bole of  the  trees of diameter  35 cm is ranging from 10-15 m long.4. Futher research on  the increment, harvesting cycle and Silviculture  techniques be conducted in order  to manage  the species sustainably.